Du numérique au digital. Documenter et valoriser les sépultures monumentales néolithiques - Serge Cassen; Valentin Grimaud (In Situ)
During the Neolithic era, the West of France was characterised by the development of monumental funerary structures and the erection of vast ensembles of steles. These are remarkable as archaeological objects since, more often than not, they are preserved in an upright position This characteristic was also the cause of their destruction, in particular from the nineteenth century. The three-dimensional representation of these ancient architectural sites was undertaken by certain early explorers but the recent development of digital tools has made it possible to establish more reliable documentation using rigorous geometric plans. The presence of engraved signs on some monolithic elements can add additional difficulties in terms of the scales of observation and of renderings, but these difficulties can now be overcome using different but complementary techniques of data acquisition. These new architectural representations raise the issue of the restoration of the ensembles, a question already raised at the end of the nineteenth century and which continues to arise where these dolmens and steles are concerned. Our contribution will take a look at two monumental tombs of a specific ‘transepted’ type, located near the Atlantic coast, one of them in the Morbihan department and the other in the Vendée. The two tombs have been recorded in 2D and 3D according to the same protocols. One has just revealed new engravings within a site that had already been restored. The other, which is threatened by the rising sea level, will be interpreted using a virtual display on a touch screen.